STUDENT ACTIVE –LEARNING: A CURRICULUM INNOVATION IN INDONESIA - Dedy Rahman Nur (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2014)
Innovation in education in Indonesia has been at a short span popular but decreased as other issues pursuing other policies dominantly present. The development of teaching models that do not match with the condition in the real implementation has made teachers confused. In addition, the curriculum contents and syllabuses that the teachers should based upon their teaching are other factors that innovation in education seem never consistently exist. This paper is a critical review on how innovation in education in Indonesia has been improperly developed.